Nitric Oxide and Temperature Measurement Using Laser Absorption Spectroscopy in Arc-Heater Plenum - Gessman, Isabella; Sub Lee, Gyu; Kato, Nozomu; Lee, Tonghun; Ghanekar, Shruti; Kim, Keunsoo; Yoo, Jihyung (American Institute of Aeronautics and Astronautics, 2025)
A mid-infrared tunable diode laser absorption spectroscopy (TDLAS) sensor to measure rovibrational temperature and nitric oxide (NO) mole fraction in the arc-heater plenum was developed and employed in the Arc Heated Combustion Tunnel-II (ACT-II) facility at the University of Illinois at Urbana-Champaign. From this study, TDLAS-inferred temperatures were found to differ from the conventional method to estimate temperature by over 13%. Chemical equilibrium simulations were performed at the TDLAS-inferred temperatures to understand how chemical relaxation timescales compare with plenum residence times. Results from this study show NO levels higher than equilibrium concentrations, with relaxation timescales that exceed plenum residence times. With insufficient time to reach equilibrium, elevated NO levels are expected to remain in the test gas and persist into the scramjet model.